From Boom to Crisis and Back Again: What Have We Learned? - Barry Bosworth; Susan M. Collins (Asian Development Bank Institute (ADBI), 2000)
It seems increasingly evident that the problems of the financial crisis in Asia were caused by a variety of different factors, the importance of which varied from country to country. However, according to the authors two points must be emphasized. First, the rapid movement toward capital account convertibility put severe strains on relatively unsophisticated financial systems that had previously focused on simple bank intermediation of funds between savers and investors. Second, governments were surprisingly unprepared to respond to pressures on their currencies.
hdl:11540/4114
Keywords: 330